Metode Penelitian dan Pengembangan (R&D) : Pengertian, Jenis dan Tahapan - Ade Rahayu (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2025)
Research and Development (R&D) is a systematic approach aimed at producing practical solutions through validated processes. In education, R&D is essential for developing instructional media, teaching tools, and learning models tailored to contextual needs. This study reviews the concept of R&D, the most widely adopted models, and their implementation stages through a literature-based method. Five major models are analyzed: Borg and Gall, ADDIE, 4D, Hannafin & Peck, and Dick and Carey. Each is examined in terms of procedural structure, advantages, limitations, and applicability in educational settings. Despite their distinct frameworks, all models share core phases: needs analysis, design, development, evaluation, and implementation. The analysis shows that Borg and Gall suits large-scale iterative studies, ADDIE is valued for its simplicity and flexibility, 4D is effective for instructional tool development, Hannafin & Peck aligns with technology-based media, and Dick and Carey supports systematic instructional design. The findings emphasize the importance of selecting models based on goals, product complexity, and resource availability. This article contributes to guiding researchers and educators in applying appropriate R&D methodologies in educational practice.